New Alternative in the Methodology of Extraction and Dyeing with Active Molecules Derived from Vegetal Sources. (2016) - Coman, Diana; Vrinceanu, Narcisa; Dinu, Milena; Cipaian, Remus Calin
Abstract: The general objective of this study refers to the identification of a sustainable and physical methodology of extraction of active compounds, envisaging the preservation of the high purity active natural dye molecule from nut shell (juglone), even under the conditions of an extraction performed in a mixt solvent medium (water-ethanol). The second major objective of the study consists of the application of these above mentioned dyes onto natural and synthetic substrates, thus making a correlation between their colour attributes and the fibrous composition of the substrates they are applied on. The motivation of this research was given by the identification of an improved extraction methodology that can increase the percentage of active parts of the plant cell wall. The efficacy of the extraction protocol in a water-ethanol solvent medium from nut shells is evidenced by the complex system of investigations: HPLC chromatography, FT-Raman and IR spectroscopy. HPLC chromatography reveals an efficient ecologic extraction procedure. Moreover, the refluxing duration in the experimental protocol of juglone extraction in a water-ethanol solvent medium from nut shells is almost the same as that belonging to synthetic juglone.